Clinical management, ethics and informed consent related to multi‐gene panel‐based high throughput sequencing testing for platelet disorders: Communication from the SSC of the ISTH. (1st October 2020) - Downes, Kate; Borry, Pascal; Ericson, Katrin; Gomez, Keith; Greinacher, Andreas; Lambert, Michele; Leinoe, Eva; Noris, Patrizia; Van Geet, Chris; Freson, Kathleen
Abstract: Molecular diagnostics of inherited platelet disorders (IPD) has been revolutionized by the implementation of high‐throughput sequencing (HTS) approaches. A conclusive diagnosis using HTS tests can be obtained quickly and cost‐effectively in many, but not all patients. The expanding use of HTS tests has raised concerns regarding complex variant interpretation and the ethical implications of detecting unsolicited findings such as variants in IPD genes RUNX1, ETV6, and ANKRD26, which are associated with increased leukemic risk. This guidance document has been developed and written by a multidisciplinary team of researchers and clinicians, with expertise in hematology, clinical and molecular genetics, and bioethics, alongside a RUNX1 patient advocacy representative. We recommend that for clinical diagnostics, HTS for IPD should use a multigene panel of curated diagnostic‐grade genes. Critically, we advise that an HTS test for clinical diagnostics should only be ordered by a clinical expert that is: (a) fully aware of the complexity of genotype‐phenotype correlations for IPD; (b) able to discuss these complexities with a patient and family members before the test is initiated; and (c) able to interpret and appropriately communicate the results of a HTS diagnostic report, including the implication of variants of uncertain clinical significance. Each patient should know what an HTS test could mean for his or her clinical management before initiating a test. We hereby propose an exemplified informed consent document that includes information on these ethical concerns and can be used by the community for implementation of HTS of IPD in a clinical diagnostic setting. This paper does not include recommendations for HTS of IPD in a research setting.